Healing leadership: the serving leader's impact on patient outcomes in a clinical environment - Andenoro A; Nagel C (Dove Medical Press, 2012)
Chris Nagel1, Anthony C Andenoro21Medical Operations – Continuous Improvement, Cleveland Clinic, Cleveland, OH; 2Department of Organizational Leadership, Gonzaga University, Spokane, WA, USAAbstract: The future of health care is a topic that has significant importance to patients and caregivers alike for generations to come. As the health care industry becomes more complex, leadership and the examination of how to most effectively apply it to meet efficiency standards and optimize the patient experience will become paramount. Through this paper the authors provide the foundation for meeting this need through an innovative and socially adept framework that identifies the critical character attributes of a serving leader and the powerful impact that serving leaders can have on patient outcomes in the health care setting. This framework is grounded in a leadership theoretical foundation and contextually examined through qualitative methods. As the business of health care becomes more complex and more competitive, finding ways to improve processes and create healing environments conducive to improved patient outcomes will differentiate average health care and excellent health care in the future. This paper provides the impetus for successfully addressing these needs through the development of serving leaders, and three specific characteristics: emotional care, presence, and awareness.Keywords: servant leadership, health care, patient outcomes